2008
DOI: 10.3189/172756408784700671
|View full text |Cite
|
Sign up to set email alerts
|

Extreme intra-seasonal anomalies in the Amundsen and Bellingshausen sea-ice area, Antarctica, during the austral winter

Abstract: We examine the role of the propagation of atmospheric mid-latitudes wave trains in modulating the Amundsen and Bellingshausen sea-ice area (SIA), Antarctica, on intra-seasonal timescales (20-100 days). Spectral analysis of passive microwave estimates of SIA in the Amundsen and Bellingshausen Seas for 1979-2004 shows significant peaks on intra-seasonal timescales. Previous studies have suggested that variations in SIA are linked to disturbances in atmospheric circulation and sea surface temperature. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Yu et al (2011) identificaram dois períodos importantes na variabilidade da temperatura do ar a 2m na Antártica e no Oceano Austral em 29 invernos utilizando dados das reanálises II do NCEP/NCAR: 26-30 dias e 13-14 dias. No entanto, Lima e Carvalho (2008) observaram o mesmo sinal encontrado no presente estudo nas anomalias de gelo marinho nos mares de Amundsen e Bellingshausen. Pelo fato do pico espectral IS estar próximo da escala temporal da MJO (entre 20-100 dias), os EIF e EIQ foram separados em MJO e NMJO (ver a explicação em "Dados e Metodologia") para avaliar a influência desta oscilação nos eventos IS de Tsup na Península Antártica em cada estação do ano (Tabela 2).…”
Section: Resultsunclassified
“…Yu et al (2011) identificaram dois períodos importantes na variabilidade da temperatura do ar a 2m na Antártica e no Oceano Austral em 29 invernos utilizando dados das reanálises II do NCEP/NCAR: 26-30 dias e 13-14 dias. No entanto, Lima e Carvalho (2008) observaram o mesmo sinal encontrado no presente estudo nas anomalias de gelo marinho nos mares de Amundsen e Bellingshausen. Pelo fato do pico espectral IS estar próximo da escala temporal da MJO (entre 20-100 dias), os EIF e EIQ foram separados em MJO e NMJO (ver a explicação em "Dados e Metodologia") para avaliar a influência desta oscilação nos eventos IS de Tsup na Península Antártica em cada estação do ano (Tabela 2).…”
Section: Resultsunclassified
“…By means of complex empirical orthogonal functions (CEOFs), Baba et al (2006) reported that the largest amplitudes in variability along the marginal sea-ice zone occurred around West Antarctica, especially in the Amundsen and Bellingshausen seas, and that the spatial phase of the meridional wind velocity preceded that of sea-ice concentration by about 908. Lima & Carvalho (2008) demonstrated the relationship between mid-latitude atmospheric wave train and sea-ice area in the Amundsen and Bellingshausen seas and showed that the extreme sea-ice area anomalies on intraseasonal timescales (20 Á 100 days) lag behind the propagation of subtropical wave train in the Southern Hemisphere by approximately 10 Á 15 days.…”
Section: Earlier Work On Antarctic Intraseasonal Variabilitymentioning
confidence: 96%
“…Mo & Higgins (1998) related the PSA to tropical convection and outgoing longwave radiation (OLR). The intraseasonal variation in tropics and subtropics is associated with atmospheric and oceanic variability in the Southern Ocean (Matthews & Meredith 2004;Lima & Carvalho 2008).…”
Section: Earlier Work On Antarctic Intraseasonal Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the persistence of the extremes was considered as the consecutive occurrence of 2 days or more, satisfying the conditions for SIE HF extremes, and as independent events, only those with at least 2 days apart (cf. Lima and Carvalho, 2008).…”
Section: High-frequency Extreme Events Of Sea Icementioning
confidence: 99%